Demographic differences in perceptions of media brand personality: a multilevel analysis. Issue 2 (3rd April 2018) - Kim, Danny Da Eun
ABSTRACT: Empirical studies from a variety of fields suggest that perceptions of the same stimuli can vary across gender, race/ethnicity, political ideology, or other demographic dimensions. This may also be the case for perceptions of media brands, but no systematic examination of demographic differences in perceptions of media brand personality across multiple media formats has previously been undertaken, in spite of potential ramifications in the context of targeted brand advertising. The present study applies multilevel regression models to personality ratings of 100 TV show, movie, video game, pop music, and news outlet brands (N = 4, 967), examining how individual-level demographic factors are associated with differing perceptions of brand personality across the dimensions of Aggression, Heroism, and Warmth. Significant ideology, gender, race/ethnicity, and familiarity effects are observed, with the results carrying relevance regarding the development of targeted and tailored messages to maximize brand-self congruence and associated effects on behavioral and attitudinal outcomes.